Leadership development: an experiential learning approach for engineering students - Giacomassi, Rafael (2018)
Lots of companies recognize the need for leadership development. However, there is still not a consensus about what practices or bundle of practices can be used for the effective development of leadership competencies. Many existing methods are focused on emulation of characteristics of successful leaders or the development of personal competencies based, for example, on psychological traits tests. Therefore, a better understanding of the application of more holistic methods for leadership development is necessary. Such methods consider personality traits as well as the organizational context where leaders are inserted. Some recent theories that have contributed to this area include Authentic Leadership Development (ALD) and Positive Organizational Scholarship (POS). Furthermore, emotional and social intelligence continue to be highly relevant subjects for leadership development because of the correlation between these attributes and leaders\' performance. This study proposes a leadership development program that encompasses fundamental concepts related to the implementation of practices that are considered suitable for organizations and individuals. The focus on the development of positive behaviors instead of the identification and resolution of imperfections is a characteristic of the proposed program. The research includes four steps: research motivation and goals definition, literature review, action research, and final considerations and conclusion. The action research step included two iterations in which the program was tested and optimized according to the learning process of the researcher. The program was offered to engineering students due to the necessity for leadership development for these future professionals and due to the lack of disciplines focused on leadership development in the engineering curriculum. Thus, the study aims to achieve a better understanding of leadership development and the implementation of practices for leadership development in engineering. Finally, a detailed syllabus of the proposed leadership development course and a method for evaluating the program is presented along with the insights acquired in the action research and recommendations for future research.